2008
DOI: 10.1080/08880010802313632
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Access Ports in Children Treated for Hematopoietic Malignancies

Abstract: During past 10 years 234 central venous access ports (CVAP) were implanted in 225 patients at the Department of Pediatric Hematology and Oncology in Zabrze. Mean exposure time was 745 days and total implantation time reached 173,768 days. Complications were encountered in 17 patients (7.6%). This mainly concerned central venous line infection, which led to removal of 10 CVAP (4.4%). The remaining complications necessitating removal of the CVAP consisted mainly of mechanical problems (catheter fracture, occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Although supportive care has improved, including antibiotic therapy during neutropenic fever, treatment‐related infections still cause significant morbidity and mortality . Treatment‐related mortality may occur in up to 3–5% of patients with leukaemia or lymphomas and is mainly caused by infections .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although supportive care has improved, including antibiotic therapy during neutropenic fever, treatment‐related infections still cause significant morbidity and mortality . Treatment‐related mortality may occur in up to 3–5% of patients with leukaemia or lymphomas and is mainly caused by infections .…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate chemotherapy administration, as well as supportive care and blood sampling, the vast majority of children diagnosed with cancer are now provided with a central venous catheter (CVC; ). Despite their great benefits, CVCs can also be hazardous, as they are a common source of serious blood stream infections .…”
Section: Introductionmentioning
confidence: 99%
“…With intraluminal fibrin deposition, the risk of coagulase-negative staphylococci infection increases (van Rooden, Schippers, Guiot, et al, 2008). Over time, occlusion occurs in 3% to 36% of patients (Bucki et al, 2008;Dal Mollin, Guerretta, Mazzufero, & Rasero, 2009;Dillon et al, 2004;Kuhle et al, 2003;Ociepa, Maloney, Urasinski, & Sawicki, 2010) and has been shown to enhance the risk of infection (Jacobs, 2003).…”
Section: Review Of Literaturementioning
confidence: 99%